Association between adiposity indicators, metabolic parameters and inflammatory markers in a sample of female adolescents - Coutinho,Priscilla Rizental (2015)
Objective The aim of this study was to investigate the association between total and abdominal adiposity with metabolic parameters and inflammatory markers, in female adolescents.Subjects and methods The sample consisted of 53 adolescents aged 13 to 17 years from a public school in Curitiba, Brazil. The adiposity indicators studied were body mass index (BMI), waist circumference (WC), trunk fat mass (TKFM), total fat mass (TFM) and body fat percentage (BF%) measured by dual-energy X-ray absorptiometry. The metabolic and inflammatory parameters studied were systolic blood pressure (SBP), diastolic blood pressure (DBP), glucose, insulin, homeostasis model assessment index for insulin resistance (HOMA-IR), lipids, C-reactive protein (CRP), interleukin-6 (IL-6), tumor necrosis factor alpha (TNF-α), leptin, adiponectin and resistin.Results Eighty percent of WC variation, 87% of TKFM and TFM, and 73% of BF% were predicted by BMI variation. There was a significant positive correlation between all indicators of adiposity with SBP, DBP, insulin, HOMA-IR, CRP and leptin. Triglycerides were positively correlated with BMI and WC, and adiponectin correlated negatively with BMI. TNF-α, IL-6, glucose, total cholesterol, and high- and low-density lipoprotein cholesterol did not correlate to the studied variables.Conclusion BMI showed a significant association with most of the parameters studied, and WC was slightly better than BMI to predict insulin resistance in this specific population.